Computational Sentiment Analysis of User Interactions on Live Streaming Platforms Using Artificial Expert Judgment - Muhamad Sandy Saputra; Ridwan Sanjaya (SISFORMA, 2026)
This study examines user interaction patterns on JKT48 Showroom live streaming using sentiment analysis on 14,857 interactions processed with a Large Language Model. The results show that most interactions are neutral (93.63%) with positive and negative sentiments appearing in smaller proportions. This suggests that user participation is mainly routine and reflects a form of “silent loyalty”. The findings highlight the importance of maintaining a stable user experience to support long term engagement.